Evli bireylerin mutluluk düzeyleri ile özgünlük ve değerler arasındaki yordayıcı ilişkiler - Yavaşoğlu, Efendi (İstanbul Sabahattin Zaim Üniversitesi, Sosyal Bilimler Enstitüsü, Eğitim Bilimleri Anabilim Dalı, 2019)
Bu çalışmanın amacı, evli bireylerin mutluluk düzeyleri ile özgünlük ve değerler arasındaki yordayıcı ilişkileri incelemektir. Araştırmada, evli bireylerin mutluluk düzeyleri ile özgünlük ve değerler arasındaki yordayıcı ilişkilerin belirlenmesi ve değişkenler arasındaki ilişkilerin yapısal eşitlik modeli ile sınanması amacıyla yapısal eşitlik modellemesi analizi yapılmıştır. Ölçekler, 2017-2018 yıllarında İstanbul’da yaşayan evli bireylerden oluşmaktadır. Araştırma da 697’ı kadın, 208’u erkek olmak üzere toplam 905 birey yer almıştır. Araştırmada Doğan ve Akıncı Çötok’ın (2011) “Oxford Mutluluk Ölçeği- Kısa Formu”, Dilmaç (2007) tarafından geliştirilen “İnsani Değerler Ölçeği” ve İlhan, T., ve Özdemir, Y. (2013) tarafından geliştirilen“Otantiklik Ölçeği” kullanılmıştır. Verilerin analizinde Amos 19 programı kullanılmıştır. Ayrıca toplanan verilerin yüzde ve frekans hesapları SPSS 18 paket programı ile gerçekleştirilmiştir. Elde edilen bulgulara göre; evli bireylerin mutluluk düzeyleri ile değerler arasındaki yordayıcı ilişkiler incelendiğinde, Değerlerin evli bireylerin mutluluk düzeylerini yordadığı, aradaki ilişkinin de pozitif yönlü ve doğrusal bir ilişki olduğu görülmektedir. Evli bireylerin mutluluk düzeyleri ile özgünlük düzeyleri arasındaki yordayıcı ilişkiler incelendiğinde, özgünlüğün mutluluk düzeyini yordadığı, aralarındaki ilişkinin pozitif yönlü ve doğrusal olduğu görülmüştür.

The aim of this study is to examine the predictive relationships between the happiness levels of married individuals and their authenticity and values. In the study, structural equality modeling analysis has been conducted in order to determine the predictive relationships between the happiness levels of the married individuals and the authenticity and values and to test the relations between the variables with the structural equation model. The scales consist of married individuals living in Istanbul in 2017-2018. A total of 905 individuals, 697 of whom are women and 208 of whom are men, have been included in the study. In the research, Doğan and Akıncı Çötok’s (2011) “Oxford Happiness Scale - Short Form, ”Human Values Scale“ which was developed by Dilmaç (2007) and ”Authenticity Scale” which was developed by İlhan T. and Özdemir Y. (2013) have been used. Amos 19 program has been used to analyze the data. In addition, the percentage and frequency calculations of the collected data have been performed by SPSS 18 package program. According to the findings; When the predictive relationships between the values of happiness levels of married individuals and values are examined, it is seen that the values predict the happiness levels of married individuals and the relationship between them is a positive and linear relationship. When the predictive relationships between the levels of happiness and the levels of authenticity are examined, it has been found that authenticity predicts the level of happiness and the relationship between them is positive and linear.
The predictor relationships between happiness levels of married individuals, authenticity and values
Pozitif Psikoloji
Mutluluk
Mutluluğun Nedenleri.
Mutluluğu Etkileyen Faktörler
Keywords: Mutluluk; Değerler; Özgünlük; Happiness; Values; Authenticity